S-밴드용 원형 마이크로스트립 패치 2×2 배열 안테나의 설계 - 안용복; 최병하; Ahn, Yong-Bok; Choi, Byoung-Ha (한국항행학회논문지, 2007)
In this paper, we have designed and fabricated microstrip antenna of S-band for the wireless LAN and the ISM. It array $2{×}2$ circular patch antenna elements at plane instead of conventional rectangular patch antenna elements. It optimized to size calculated of single patch antenna. The radiation elements distance is array $0.24λ$. The fabricated circular patch antenna decreased 8% of size compared to the conventional rectangular patch antenna. In the E-plane, designed circular microstrip patch $2{×}2$ array antenna gain is 12.7[dBi], half power beam width is $40^{°}$ and in the H-plane, antenna gain is 12.1[dBi], half power beam width is $45^{°}$. Bandwidth is 250[MHz] (VSWR < 2). 본 논문에서는 ISM(Industrial, Scientific, Medical)대역과 Wireless LAN대역을 위한 S-band에서 동작하는 마이크로스트립 안테나를 설계 및 제작을 하였다. 기존의 사각패치 안테나 소자가 아닌 원형패치 안테나 소자 4개를 평면상에 $2{×}2$로 배열하였다. 단일 원형패치의 크기를 계산하여 최적화하였으며 방사소자 간의 간격을 $0.24λ$로 배열하였다. 원형패치 안테나 소자를 사용함으로써 기존의 사각패치 안테나 소자를 이용한 것 보다 8%의 크기를 감소시켰다. 제안된 안테나는 E-평면에서는 안테나 이득 12.7 [dBi], 3 dB 빔폭은 $40^{°}$를 나타냈으며 H-평면에서는 안테나 이득 12.1 [dBi], 3 dB 빔폭은 $45^{°}$라는 특성을 나타내었으며, 250[MHz]의 대역폭 (VSWR < 2)을 얻었다.